Profitability of the Banking Sector in Poland between 2015 - 2019 - Dondalski, Paweł; Ostrowska, Aleksandra (Olsztyn Economic Journal, 2020)
Our research objective was to assess how the main profitability indicators of the banking sector have been used in Poland in the years 2015 - 2019 and to analyse the elements that make up their value. Return on assets (ROA) and return on equity (ROE) were used to measure the profitability of the banking sector in Poland. The research methods used included an analysis of available literature and statistical data published by the Polish Financial Supervisory Authority, the National Bank of Poland and the European Central Bank. We used dogmatic, statistical, and comparative methods. We put forward the following research hypothesis: the reason for the decrease in profitability of the Polish banking sector in the face of the growing profits was the increase in the value of assets and equity. The research results confirmed this hypothesis. The reasons for the decreasing profitability of banks in Poland included excessively low levels of generated profits in relation to the increase in the value of capital and assets. Moreover, we identified the factors influencing this phenomenon.